The Relationship between Service Delivery and Work Engagement on Nurse Performance at Bali Mandara Hospital 2022 - Komang Lynda Octavina Permatasari; Puput Oktamianti (Syntax Corporation Indonesia, 2023)
Nursing services are the center of attention in every hospital because this service is a main activity that can be used as a benchmark for evaluating health services, especially in inpatient rooms. Performance measurement is carried out to improve the quality of providing nursing care, reduce costs, protect nurses from negligence in carrying out their duties, and protect patients from negligence in health services. Achievement of Indicators based on the Work Plan at Bali Mandara Hospital in 2021 with the performance indicator of the Percentage of Services program that meets Standard Operating Procedures is targeted to reach 100% and the realization reached 85.45%. In 2021, the target of providing salaries and benefits for health workers is 90%, and 87.07% is achieved. The research objective was to determine the relationship between service delivery and work engagement on the performance of inpatient nurses. This study used an observational design with a cross sectional. The number of samples selected was 241 people. Data analysis used multiple logistic regression test. The results showed that there was a significant relationship between service delivery and work engagement on nurse performance. Variable work engagement is the most dominant variable influencing the performance of inpatient nurses at Bali Mandara Hospital.